Estimating the Impact of Trade and Offshoring on American Workers Using the Current Population Surveys - Ebenstein, Avraham (2012)
The authors link industry-level data on trade and offshoring with individual-level worker data from the Current Population Surveys. They find that occupational exposure to globalization is associated with larger wage effects than industry exposure. This effect has been overlooked because it operates between rather than within sectors of the economy. The authors also find that globalization is associated with a reallocation of workers across sectors and occupations. They estimate wage losses of 2 to 4 percent among workers leaving manufacturing and 4 to 11 percent among workers who also switch occupations. These effects are most pronounced for workers who perform routine tasks.